Estimating Trade Flows, Describing Trade Relationships, and Identifying Barriers to Cross-Border Trade Between Cameroon and Nigeria - World Bank (Washington, DC, 2014)
Cameroon and Nigeria share a common border of nearly 1,700km and both countries have strong historical and cultural ties. However, the partnership between the two countries has had its difficult periods, most recently when the relationship turned hostile over the disputed Bakassi Peninsula, and economic linkages between the economies remain limited. Expanding trade between the two countries could play a critical role in accelerating economic development and regional integration by opening up new markets for producers, and allowing them to benefit from economies of scale. This will require reducing barriers to cross-border trade, allowing increased trade flows to reach the larger market, and permitting private sector producers to increase the scale of their activities. Removing barriers to trade between the two neighbors is likely to benefit particularly relatively remote areas of both countries. The study finds that regulatory and security barriers at the border and along the road remain key impediments to trade. The remainder of this report proceeds as follows. Section one describes drivers for cross border trade such as historical relations, economic factors, and the policy environment. The next section describes the reality of trade flows by describing existing trade corridors and estimating current trade flows. Section three describes how goods are actually traded across borders between the two countries, and how different actors are involved. Section four describes the barriers to trade, and identifies which barriers are most important. Section five describes the potential for increasing trade. Section six summarizes the findings and presents prioritized recommendations for policy reform.